2016
DOI: 10.1002/2016jg003473
|View full text |Cite
|
Sign up to set email alerts
|

Optimal allocation of leaf‐level nitrogen: Implications for covariation of Vcmax and Jmax and photosynthetic downregulation

Abstract: The maximum rate of carboxylation, Vcmax, and the maximum rate of electron transport, Jmax, describe leaf‐level capacities of the photosynthetic system and are critical in determining the net fluxes of carbon dioxide and water vapor in the terrestrial biosphere. Although both Vcmax and Jmax exhibit high spatial and temporal variability, most descriptions of photosynthesis in terrestrial biosphere models assume constant values for Vcmax and Jmax at a reference temperature ignoring intraseasonal, interannual, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…This is the ‘strong form’ of the co‐ordination hypothesis (Chen et al, ; Haxeltine & Prentice, ; Maire et al, ), contrasting with a ‘weak form’ that assumes that the total metabolic N content of the leaf is prescribed so that only the allocation of N to carboxylation versus electron transport capacities is optimized (e.g. Quebbeman & Ramirez, ). In response to environmental variations, the co‐ordination hypothesis predicts vertical variation of V cmax,tg within the canopy, geographic variation among sites and temporal variations with atmospheric CO 2 concentration and climate (Haxeltine & Prentice, ; Smith et al, ; Terrer et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…This is the ‘strong form’ of the co‐ordination hypothesis (Chen et al, ; Haxeltine & Prentice, ; Maire et al, ), contrasting with a ‘weak form’ that assumes that the total metabolic N content of the leaf is prescribed so that only the allocation of N to carboxylation versus electron transport capacities is optimized (e.g. Quebbeman & Ramirez, ). In response to environmental variations, the co‐ordination hypothesis predicts vertical variation of V cmax,tg within the canopy, geographic variation among sites and temporal variations with atmospheric CO 2 concentration and climate (Haxeltine & Prentice, ; Smith et al, ; Terrer et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found a significant correlation between leaf V cmax and leaf N content in different ecosystems (Crous et al, 2008;Kattge et al, 2009;Quebbeman & Ramirez, 2016;Ripullone et al, 2003), due to a large amount of total leaf N (15-35%) that is allocated to Rubisco protein in C 3 plants (Evans, 1989b;Feng & Dietze, 2013). Consequently, many TBMs adopted fixed relationships between V cmax and leaf nitrogen content to constrain photosynthetic capacity (Dietze, 2014).…”
Section: The Role Of Leaf Nitrogen In Subtropical Evergreen Coniferoumentioning
confidence: 99%
“…Additionally, recent work using the coordination theory of photosynthesis (e.g. Wang et al 2017, Quebbeman andRamirez 2016) suggests that plants adjust carboxylation-and electron transport-limited photosynthetic processes such that neither is strongly limiting at current growth conditions. It is possible that similar acclimation of export-limited photosynthesis occurs, though more measurements are needed to fully assess this response.…”
Section: Low Tpu Limitationmentioning
confidence: 99%